2023
DOI: 10.1021/acsapm.3c00341
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Electromagnetic Interference Shielding of PPA6@NiM/PDMS Composites with Porous and Asymmetric Gradient Structures

Abstract: In this work, magnetic PA6 microspheres (PPA6@ NiM) with porous structures were prepared using the solvent coprecipitation method and electroless nickel plating technology, and the stacked magnetic microspheres were encapsulated with polydimethylsiloxane (PDMS) to obtain PPA6@NiM/PDMS composites. The existence of the porous structure increases the attenuation path of the electromagnetic wave, and the presence of the nickel layer improves the magnetic loss of the composite material to the electromagnetic wave a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
(79 reference statements)
0
0
0
Order By: Relevance
“…Yu et al [169] prepared PI(polyimide)/Ti 3 C 2 Tx Mxene/AgNW(silver nanowire) composite through electrostatic spinning and a hot-press approach. Wu et al [170] obtained PPA6@NiM(magnetic PA6 microspheres)/PDMS composite using the solvent coprecipitation method. Chu et al [171] prepared h-PANI/CNF/Mxene composite films with the alternating vacuum-assisted filtration method.…”
Section: Layered Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al [169] prepared PI(polyimide)/Ti 3 C 2 Tx Mxene/AgNW(silver nanowire) composite through electrostatic spinning and a hot-press approach. Wu et al [170] obtained PPA6@NiM(magnetic PA6 microspheres)/PDMS composite using the solvent coprecipitation method. Chu et al [171] prepared h-PANI/CNF/Mxene composite films with the alternating vacuum-assisted filtration method.…”
Section: Layered Structurementioning
confidence: 99%
“…Guo et al [172] obtained ANF(aramid nanofiber)/AgNW/GN composite films through a vacuum filtration and hot-press approach. They found that the electromagnetic shielding material with a layered structure exhibited a strong absorbing ability, primarily attributed to the formation of a dense conductive network in the core layer of the material and excellent adhesion between the layers [42,[169][170][171][172]. Table 4 shows the recent research of layered-structured electromagnetic shielding materials.…”
Section: Layered Structurementioning
confidence: 99%